An Overview Of Tuberculosis Chemotherapy - A Literature Review - Susmita Sarkar; Mavanur R Suresh (Frontiers Media S.A., 2011)
Tuberculosis (TB) is a major threat in global public health. The emergence of HIV and also multi drug resistant (MDR) and extremely drug resistant (XDR)-TB poses a vital challenge to the control of the disease. For the last 40 years, no new anti-TB drug has been discovered. This literature review provides a brief discussion of existing drugs and emerging drug targets, and also of the advantages of incorporating modern drug delivery systems and immune modulators in order to improve the existing treatment regimen in terms of better efficacy, reduced drug administration frequency, shortened period of treatment and reduced drug related toxicity. The investigation for new a drug target is essential in carrying on the fight against MDR and XDR-TB. However, owing to the enormous cost and time involved in new drug development, improvement of the existing treatment regimen is seen to be a valid alternative. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.